Municipality-Level Source Apportionment of PM2.5 Concentrations based on the CAPSS 2016:(I) Gyeonggi Province - You, Seunghee; Bae, Changhan; Kim, Hyungcheon; Yoo, Chul; Kim, Soontae (Journal of Korean Society for Atmospheric Environment, 2020)
Abstract Emissions of SOx, NOx, NH3, volatile organic compounds and primary PM2.5 released from thirty-one local authorities in Gyeonggi and its adjacent provinces were tagged to estimate the inter-and intra-provincial contributions as well as the self-contributions to the annual mean PM2.5 concentrations for 2016. The CAMx-PSAT simulation with the Clean Air Policy Support System 2016 at horizontal grid resolutions of 27 km, 9 km, and 3 km was applied. During the two-way nesting simulation, coarser modeling domains were utilized to quantify the contributions of emissions from the upwind foreign countries (foreign contribution) to PM2.5 concentrations in Gyeonggi’s local authorities. Results show that the foreign contributions to PM2.5 concentrations of local authorities in Gyeonggi during 2016 ranged from 50~76%, exhibiting higher foreign contributions to local authorities in northwestern Gyeonggi due to their geographical locations vulnerable to the long-range transport of air pollutants and relatively low self-contributions (contributions of local authorities’ emissions). Self-contributions to PM2.5 concentrations for the local authorities varied in the range of 2~12% (mean 6%). In comparison, the intra-contribution (contributions of emissions from the rest of Gyeonggi) ranged from 8~20% (mean 13%) during the yearlong simulation period. On the other hand, the total inter-provincial contributions (contributions of emissions from neighboring provinces such as Seoul, Incheon, Chungcheong, and Gangwon) amounted to Gyeonggi’s PM2.5 by 17% on average. However, for a specified local authority in Gyeonggi, the inter-provincial contributions to the PM2.5 concentrations were as high as 27%, possibly due to its proximity to high emission areas outside the province. In the meantime, the modeled contributions of Gyeonggi’s emissions to the PM2.5 concentrations of its surrounding provinces were 4~11%. It implies mitigations on the inter-and intra-provincial contributions are important to improve PM2.5 concentrations in Gyeonggi’s local authorities. It also represents that emission control plans across the provinces are inevitable to improve the local PM2.5 concentrations in and around Gyeonggi.
Keywords: Foreign contribution; Inter- and intra-provincial contributions; Local authorities in Gyeonggi; PM2.5; Self-contribution